Origin of structural parameter inconsistency in forward osmosis models: A pore-scale CFD study - Kang, Peter K.; Lee, Woonghee; Lee, Seockheon; Kim, Albert S. (ELSEVIER, 2017)
Structural parameter is a representative quantity of a porous medium, often used to explain mass transfer rate in membrane processes. Intrinsic structural.parameter is defined using characteristic constants of a porous medium, and effective structural parameter is indirectly obtained by analyzing measured fluxes, especially in osmosis driven processes. Although the two parameters are fundamentally equivalent, recent experimental studies show noticeable discrepancies between them. To resolve the inconsistency, we hypothesize that the fraction of effective membrane surface area should include interfacial porosity between the active layer and the porous substrate. To test our hypothesis, we develop a new pore-scale CFD (computational fluid dynamics) solver for both mass and momentum transfer in transient forward osmosis phenomena. Two pre-existing solvers of OpenFOAM, an open-source computational fluid dynamics software package, are combined to seamlessly link the coupled transport phenomena across the active layer, the support layer, and the crossflow zone. We defined a new structural parameter using the simulated flux and the interfacial porosity, first addressed in this study, and obtained an excellent agreement between our CFD results and published experimental data in the literature.
Keywords: INTERNAL CONCENTRATION POLARIZATION; THERMOPHYSICAL PROPERTIES; MEMBRANE-STRUCTURE; FLUX BEHAVIOR; PERFORMANCE; TRANSPORT; COMPOSITE; WATER; DESALINATION; SIMULATIONS